Diffusion and adsorption selectivities of hydrocarbons over FCC catalysts - Avila, Adolfo María (2007)
The adsorption isotherms of hexane, toluene and decane on a commercial FCC catalyst were determined in experiments performed in a CREC Riser Simulator laboratory reactor injecting different volumes of the pure hydrocarbons at 250, 300 and 350 °C. The adsorption isotherms could be described by Langmuir expressions, and the parameters assessed from the information given by simple mass balances, showed to be in line with previous reports. The order of adsorption constants was decane > toluene > hexane. The heats of adsorption were assessed. The simulation of the evolution of the pressure in the system in short contact time experiments with an unsteady state diffusion-adsorption model that considered the influence of the concentration on diffusion, allowed to assess the diffusion parameters corresponding to diluted systems. It was observed that the mechanism for mass transfer of n-paraffins inside the Y zeolite pores above 250 °C is not purely configurational. Experiments with short contact times typical of the commercial FCC process showed that decane and toluene, but not hexane, were adsorbed close to equilibrium under these experimental conditions. Apparent and equilibrium adsorption, and diffusion selectivities were defined considering hexane as the reference hydrocarbon, and they clearly indicated that diffusion resistances mask the assessment of adsorption parameters. Apparent selectivities become closer to equilibrium selectivities at higher system pressures, due to increases in the effective diffusivities.